Lama Penyangraian Terhadap Sifat Fisiko-Kimia Biji Kopi Arabika Nagari Lasi Kecamatan Canduang Kabupaten AgamProvinsi Sumatera Barat - Rafki Adey Ilham; Farida Hanum Hamzah; Raswen Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Roasting is the process of forming flavor to coffee beans which is carried out using high temperatures. Currently, there is still little data on how the proper roasting.  This research was conducted to determine the effect of roasting time on changes in the physico-chemical properties of Arabica coffee. The research design used was a completely randomized design (RAL) non factorial with roasting time treatment consisting of 10 minutes, 12 minutes, 14 minutes, 16 minutes, and 18 minutes. The results showed that the roasting time had an effect on moisture content, ash content, degree of acidity, caffeine content, hedonic aroma, and arabica coffee color. Roasting temperature of 220°C with roasting time of 10 minutes was the best treatment to produce the best physical characteristics and quality of arabica coffee, namely with a water content of 2.41%, 4.09% ash content, 4.87 degree of acidity, 2.54% caffeine content, aroma scoring 3.80, color L 25,97.Keywords: Arabica coffee, roasting, roasting duration